Answer:
(- 2, - 4 )
Explanation:
Given the 2 equations
3x - 2y = 2 → (1)
5x - 5y = 10 → (2)
Multiply (1) by 5 and (2) by - 3, then add to eliminate x
15x - 10y = 10 → (3)
- 15x + 15y = - 30 → (4)
Add (3) and (4) term by term to eliminate x , that is
5y = - 20 ( divide both sides by 5 )
y = - 4
Substitute y = - 4 into either of the 2 equations and solve for x
Substituting into (1)
3x - 2(- 4) = 2
3x + 8 = 2 ( subtract 8 from both sides )
3x = - 6 ( divide both sides by 3 )
x = - 2
Solution is (- 2, - 4 )